Maps of native ranges of tropical and subtropical plants created by GIS - Dobesova, Zdena; Vavra, Ales; Dancak, Martin (Geodesy and Cartography, 2017)
This article presents various methods employed for construction of maps of native ranges of plants using geographical information system (GIS). The maps were originally created for a set of publications on important tropical and subtropical plants species kept in the collections of Flora Olomouc Exhibition Grounds, JSC., Czech Republic. Two different approaches were applied using outlined and chorochromatic methods. The former was used for construction of maps depicting approximate ranges, i.e., ranges which cannot be constructed exactly due to the objective lack of biogeographical data (e.g. early domesticated crops, which no longer occur in the wild). The latter approach was used for construction of maps showing known ranges, i.e., ranges that can be constructed more or less exactly because there is no considerable lack of biogeographical data. The maps of known ranges could be further divided according to the total area of the depicted range, its shape or location. The paper also presents plans of the greenhouses and the exhibition complex at Flora Olomouc Exhibition Grounds, using a different type of thematic maps useful for large-scale mapping of living collections.